Infant neural processing of mother’s face is associated with falling reactivity in the first year of life - Silvia Rigato; Manuela Stets; Henrik Dvergsdal; Karla Holmboe (Developmental Cognitive Neuroscience)
It is well established that faces evoke a distinct neural response in the adult and infant brain. Past research has focused on how the infant face-sensitive ERP components (N290, P400, Nc) reflect different aspects of face processing, however there is still a lack of understanding of how these components reflect face familiarity and how they change over time. Further, there are only a few studies on whether these neural responses correlate with other aspects of development, such as infant temperament. In this longitudinal study (N∼60), we recorded infant visual ERPs in response to mother and stranger face stimuli at 4, 6 and 9 months of age. Our results showed that, compared to a stranger face, the mother face evoked a larger N290 at 4 months and a larger P400 at 6 months. At 9 months, no difference was found between mother and stranger faces. However, at 9 months we found that the P400 and Nc amplitudes evoked by the mother face were associated with infant falling reactivity. We conclude that the neural responses associated with the processing of faces, and specifically the face of the mother, are related to the development of infant individual characteristics.